Lacrimal gland pleomorphic adenoma: a review of 52 cases, 15-year experience. (2nd January 2019) - Clarós, Pedro; Choffor-Nchinda, Emmanuel; Lopez-Fortuny, Marta; Zofia Sobolewska, Aleksandra; Clarós, Andres
Abstract: Background: Lacrimal gland (LG) tumours are rare neoplasms. Pleomorphic adenoma (PA) is the most common histologic variant, representing ∼20% of all LG tumours. PA tends to recur leading to great morbidity. Aims: We carried out this study to share our experience and provide recent data on the clinical aspects, radiologic findings, management and outcome after treatment. Methods: We realised a hospital-based retrospective case review including data collected from 52 patients, managed over 15 years. Results: The mean age was 39.8 ± 2 years. Unilateral painless proptosis was the most constant sign (51.9%). CT-scan showed predominantly isodense lesions (96.2%), with regular borders (94.2%), measuring on average 2 cm. MRI showed isointense lesions on T1-weighted images in 96.2% of cases. No pre-operative biopsy was done. Surgical management was mainly external lateral orbitotomy (94.2%). There was no recurrence, considering a mean follow-up period of 12.6 years. Size of tumour at the time of diagnosis increased with age (r = +0.36, p = .01). Conclusions: Clinical and radiologic characteristics are consistent with literature. Older patients seem to present larger tumours. We believe that biopsy is not necessary if appropriate imaging is done. Complete, intact resection is generally sufficient to minimise the risk of recurrence.